Eating Behaviors and Quality of Life in Preadolescents at Risk for Obesity With and Without Abdominal Pain. Issue 2 (February 2015) - Crowell, Michael D.; Murphy, Tasha B.; Levy, Rona L.; Langer, Shelby L.; Kunin-Batson, Alicia; Seburg, Elisabeth M.; Senso, Meghan; Sherwood, Nancy E.
ABSTRACT Objectives: We evaluated eating behaviors and quality of life (QOL) in preadolescent children at risk for obesity, with and without abdominal pain (AP). Methods: Participants were parent–child dyads enrolled in a randomized, controlled obesity prevention trial. The children were between 5 and 10 years of age and at risk for obesity (70th–95th percentile of body mass index, n = 420). Parents completed measures of their child's eating behaviors, QOL, AP, and bowel function and their own depression status, concern about child weight, and feeding practices. Children's height and weight were also measured. Results: Children with frequent AP (≥2/month, n = 103) were compared with children reporting infrequent AP (<2/month, n = 312). Age and body mass index did not differ between groups, but AP was more prevalent in girls. Child emotional overeating and parental depression scores were higher in the frequent AP group (P < 0.01), and child QOL was lower (P < 0.01). In multivariable analysis, female gender (odds ratio [OR] 2.18, 95% confidence interval [CI] 1.20–3.97), emotional overeating (OR 2.28, 95% CI 1.37–3.81), and parental depression (OR 1.23, 95% CI 1.12–1.35) were associated with more frequent AP. Secondary analyses were completed for children who met Rome III criteria for irritable bowel syndrome. Conclusions: Clinicians working with children with AP at risk for obesity should consider assessing for and, when appropriate, addressing parent and child factors that could exacerbate AP.